Darkedge midshipman Porichthys analis (Batrachoidiformes: Batrachoididae), a common shrimp-bycatch fish from the Gulf of California - González-Ochoa, Oscar A. (2012)
Shrimp fishery bycatch of the Gulf of California constitutes a wide variety of highly unknown fish, crustacean, and mollusk species with very low or null economic value, in contrast to those of commercial interest. However, there are no studies yet on the role of these low economic valued species have in the community structure and function, together with their possible effect on commercial populations. With the aim of contributing to the knowledge of Darkedge Midshipman fish Porichthys analis, the most common waste species in this fishery, we estimated some population characteristics. For this purpose, we obtained shrimp-bycatch fish during the 2004-2005 fishing season and performed some research surveys. A total of 1 725 Darkedge Midshipman were captured from 350 bycatch samples. Individual size ranged from 43-352mm SL. The weight to standard length relationship was determined as W=0.000092SL3.0509. Von Bertalanffy’s growth coefficient indicated a moderate growth rate (K=0.5) with an estimated asymptotic length ofL∞=352mm standard length, and a longevity of 6yr. Natural mortality was estimated as 0.97 and total mortality as 4.67. The recruitment pattern, as estimated by ELEFAN II, was extended over the year, peaking during spring and summer seasons. Sexual proportion of male:female was 1.65:1. Mature organisms appeared from August to March, and length at maturity was 157mm SL, which is larger than the mean size at capture 135mm SL. We concluded that the species is indirectly protected by its own bathymetric distribution and the off-shrimping season. This is the first study that considers population characteristics from this common but still unknown species.